Country-level effects of diagnosis-related groups: evidence from Germany's comprehensive reform of hospital payments - Robert Messerle; Jonas Schreyögg (The European Journal of Health Economics, 2023)
Hospitals account for about 40% of all healthcare expenditure in high-income countries and play a central role in healthcare provision. The ways in which they are paid, therefore, has major implications for the care they provide. However, our knowledge about reforms that have been made to the various payment schemes and their country-level effects is surprisingly thin. This study examined the uniquely comprehensive introduction of diagnosis-related groups (DRGs) in Germany, where DRGs function as the sole pricing, billing, and budgeting system for hospitals and almost exclusively determine hospital revenue. The introduction of DRGs, therefore, completely overhauled the previous system based on per diem rates, offering a unique opportunity for analysis. Using aggregate data from the Organisation for Economic Co-operation and Development and recent advances in econometrics, we analyzed how hospital activity and efficiency changed in response to the reform. We found that DRGs in Germany significantly increased hospital activity by around 20%. In contrast to earlier studies, we found that DRGs have not necessarily shortened the average length of stay.
Keywords: H51; I11; I18; L51; 610; DRG; Case-based payment; Hospital reimbursement; Hospital payment scheme; Hospital activity; Payment reform